2019
DOI: 10.1152/ajprenal.00411.2018
|View full text |Cite
|
Sign up to set email alerts
|

(Pro)renin receptor contributes to pregnancy-induced sodium-water retention in rats via activation of intrarenal RAAS and α-ENaC

Abstract: The (pro)renin receptor (PRR) is a new component of the renin-angiotensin-aldosterone system (RAAS) and regulates renin activity. The objective of the present study was to test potential roles of the renal PRR and intrarenal RAAS in the physiological status of late pregnancy. Late pregnant Sprague-Dawley rats were studied 19–21 days after sperm was observed in vaginal smears. Experiments were performed using age-matched virgin rats and late pregnant rats treated with the specific PRR inhibitor PRO20 (700 μg·kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
(57 reference statements)
0
15
0
Order By: Relevance
“…The ability of Ang II to elevate blood pressure is 10∼40 times powerful than adrenaline (24). Ang II raises blood pressure through multiple factors, mainly through stimulating zona glomerulosa of the adrenal gland, promoting aldosterone secretion and sodium-water retention (20,(25)(26)(27). Besides, it enhances noradrenaline release from sympathetic nerve endings (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of Ang II to elevate blood pressure is 10∼40 times powerful than adrenaline (24). Ang II raises blood pressure through multiple factors, mainly through stimulating zona glomerulosa of the adrenal gland, promoting aldosterone secretion and sodium-water retention (20,(25)(26)(27). Besides, it enhances noradrenaline release from sympathetic nerve endings (28).…”
Section: Discussionmentioning
confidence: 99%
“…The renin-angiotensin-aldosterone system (RAAS) is one of the systems closely related to vasomotor and sodium-water metabolism in vivo , which plays crucial roles in cardiovascular physiology and pathophysiology ( 19 , 20 ). In the RAAS, the angiotensin converting enzyme (ACE) generates Ang II, which has high bioactivity and powerful vasoconstrictor effect.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological relevance of this mechanism has been pointed out in pregnant rats. The administration of the PRR decoy inhibitor (PRO20) attenuates pregnancy-induced α-ENaC upregulation, Na + -water retention, and plasma volume expansion associated with suppressed intrarenal RAAS ( Fu et al, 2019 ). In fact, sPRR acutely stimulates ENaC activity via Nox4-derived ROS ( Wang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to the non-pregnant rats, PRR expression in the heart, aorta, and kidney tissues and 24-hour urinary sPRR excretion was significantly higher in the pregnant rats (Avila-Ramírez MA et al, 2019;Fu Z et al, 2019). A prospective cohort study showed that elevated plasma sPRR levels at early but not middle or late pregnancy were associated with the elevation of BP, and increased concentrations at delivery had a strongly increased incidence of preeclampsia (Watanabe N et al, 2012).…”
Section: Sprr May Be a Predictor Of Pregnancy Syndromementioning
confidence: 99%
“…The levels of sPRR in plasma and urine samples can be measured using a commercial sPRR enzyme-linked immunosorbent assay (ELISA) kit (Biswas KB et al, 2011;Maruyama N et al, 2013). PRO20, the first 20 amino acid residues of the prorenin prosegment, worked as a decoy PRR inhibitor to block prorenin binding to the PRR, and exhibited anti-hypertensive (Li W et al, 2015;Wang F et al, 2015;Xu C et al, 2017a), reno-protective (Fang H et al, 2018;Luo R et al, 2020), diuretic (Wang F et al, 2016), natriuretic (Fu Z et al, 2019), and anti-kaliuretic (Xu C et al, 2016;Xu C et al, 2017b) actions by targeting the RAS. However, although Li et al have demonstrated the binding affinity and specificity of PRO20 to the PRR in the mouse brain with dissociation constants (K d ) of 4.6±2.2 nM and maximum binding (B max ) of 24.0±4.1 RFU (relative fluorescence units) using FITC-labeled PRO20 peptide (Li W et al, 2015), the inhibition constant (K i ) for the binding of prorenin by PRO20 and the in vivo half-life, bioavailability, clearance rate, and the apparent volume of distribution of PRO20, are unclear and needed to be further clarified.…”
Section: / 35mentioning
confidence: 99%